Synergistic effect of pH-shifting and Maillard reaction on the structure and function of carp by-product protein isolate - Yanjun Liu; Yanan Mo; Yixiao Shen; Ling Liu (Food Hydrocolloids, 2026)

L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

Gecko tail regeneration-inspired composite hydrogel scaffolds with “socket-plug” architecture for dynamically programmed repair of infected bone defects - Minglang Zou; Yi Tang; Yongming Wang; Ling Mo; Menghuan Wang; Qing He; Zhenjin Xu; Liu Su; Pengfei Wang; Fang Luo; Da Huang; Jiewei Luo; et al. (Chemical Engineering Journal, 2026)

Seed Germination in Red Mud: Roles of Plant Traits and Metal Availability - Jian-Rui Wang; Jian-Xiong Liao; Qian-Wen Jiang; Ling Mo; Rui-Xia Ma; Jing-Jing Feng (Water, Air, & Soil Pollution, 2026)

Multidimensional analysis of pathogen epidemic patterns, their correlation with milk quality, and drug resistance and virulence traits of dominant pathogenic Escherichia coli in high-somatic-cell buffalo milk: Guangxi, China - Yifei Xiang; Zhifei Wei; Xuelian Mo; Yuying Liao; Chongli Wen; Mengyao Liao; Jiazhou Wei; Changhua Lin; Wenjing Li; Jiaji Chen; Lei Xu; Min Zhu; et al. (Food Microbiology, 2026)

Integrated analysis uncovers ALOX15 inhibition alleviates synaptic dysfunction in BDE47-associated Alzheimer's disease - Ling Mo; Xiaonian Zhu; Na Wang; Jiale Song; Jiansheng Cai; Bo Qian (Journal of Environmental Sciences, 2026)

Physiological and transcriptomic responses of Synechococcus sp. FACHB-805 to phosphite under phosphate limitation - Ye Zheng; Xingyao Ye; Xiaojun Niu; Dongqing Zhang; Mo Wang; Yang Yu; Ling Li; Chen Wang; Xiufang Yang; Xintai Su (Algal Research, 2026)

Visual working memory is impaired in Alzheimer's disease: evidence from real-world objects and perceptual organization - Xiaomeng Ma; Xiyu Mo; Binglong Li; Yiru Xu; Ling Long; Qing Dong; Zhan Ma; Qing Tian; Xiaohong Chen; Jiehui Qian (Experimental Brain Research, 2026)

Microbial and abiotic oxidation of phosphite (P(III)) in aquatic environments: pathways, controls, and ecosystem implications - Ye Zheng; Chen Wang; Dongqing Zhang; Xiaojun Niu; Ling Li; Mo Wang; Zhihong Zhang; Yang Yu; Yuhao Zhang; Cuiting Su; Jianeng Chen; Xingyao Ye (Reviews in Environmental Science and Bio/Technology, 2026)

Attenuation of antibiotics and endocrine disruptors flux along the Land-To-Sea continuum: Dominant role of terrestrial ecosystems and remediation potential of salt marsh ecosystems - Zi-Long Mo; Yi-Qin Chen; Yang Yu; Ling-Kan Su; Juan-Ying Li (Marine Pollution Bulletin, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Autophagy-dependent disruption of β-FAO-mediated histone acetylation in embryos during maternal aging - Dongmei Deng; Chong Li; Ling Zhu; Yin Tian; Jie Wang; Chenshi Li; Mo Chen; Guoning Huang; Shaorong Gao; Shimeng Guo; Jingyu Li (Science Bulletin, 2026)

Multifunctional bacterial consortium degrading phthalates, promoting plant growth and inhibiting soil-borne pathogenic fungi - Jie-bin Zhou; Qiong-Wen Zhang; Yong-Ling Zhou; Hai-Feng Chen; Yu-Hong Huang; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2026)

Dynamic assessment of NO2 plume rise and pollution contributions from steel industry point sources in an energy-intensive region of China - Chao Gao; Xuelei Zhang; Mo Dan; Ling Huang; Hongmei Zhao; Shichun Zhang; Aijun Xiu (Atmospheric Pollution Research, 2026)

Teat-Track: A real time tracking method for piglet teat counting - Wenjie Huang; Zhenfang Wu; Ling Yin; Qiong Huang; Sumin Zhang; Delin Mo; Gengyuan Cai (Biosystems Engineering, 2026)

Multiple-layered fine-tuning of flowering locus C --- Flowering control and beyond - Wenfeng Huang; Yujian Mo; Xiaolin Liang; Shusong He; Xingyu Jiang; Yu Ling (Plant Science, 2026)

Presence of per- and polyfluoroalkyl substances (PFASs) in the Nandu River Estuary, Hainan Island - Jiang-Wei Miao; Zhang-Min Jiang; Peng-Fei Xie; Jia-Xing He; Jia Xie; Hai-Long Zhou; Ling-Mo; Shi-Quan Chen; Tuan-Tuan Wang; Sai Wang (Marine Environmental Research, 2026)

Machine learning-coupled multi-elemental fingerprinting for high-accuracy source identification of distillation residues: A novel strategy for industrial waste traceability - Yiqing Sun; Qingwei Guo; Xiubao Wang; Jianwei Yue; Xiaocheng Song; Siyuan Yang; Wei Liu; Ling Mo; Li-Cheng Wang; Lingshuai Kong; Jinhua Zhan; Zhenhui Gao (Journal of Hazardous Materials, 2026)

Occurrence, landscape impact, and risk assessments of pesticides in a major river basin of a tropical island, South China - Ling Mo; Bin Tang; Li-Ke Chen; Jun Xiang; Ming-Yang Wang; Kai-Yi Wu; Ming-Zhong Ren; Qiao Xing; Li-Cheng Wang; Jing Zheng (Environmental Pollution, 2026)

Multi-head attention driven aggregation-differentiation network for probabilistic groundwater depth forecasting and depth-stratified early warning: A multi-site efficient framework - Jing Xu; Siyuan Liu; Jinran Wu; Yuming Mo; Kun Wang; Qingfeng Ji; You-Gan Wang; Ling Li (Environmental Modelling & Software, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Synergistic optimization of field management measures for yield increase and emission reduction of Panax notoginseng based on DNDC model and NSGA-III - Qiliang Yang; Liuhui Mo; Wentao Zhang; Ling Yang; Chunhao Cao; Na Li (Agricultural Systems, 2026)

Probiotic Bacillus tequilensis protected Micropterus salmoides against Aeromonas veronii infection by modulating digestion, immunity, and intestinal microbiota and metabolites - Jianqiang Huang; Jingran Sun; Ling Pan; Fuping Song; Huiqin Huang; Kunlian Mo; Yan Wang; Yonghua Hu (Aquaculture, 2026)

Coupled salt and nitrogen dynamics in coastal reservoir-adjacent aquifer systems under extreme rainfall event - Yuming Mo; Jing Xu; Yuhang Tian; Senlin Zhu; Jinran Wu; Tong Li; Guangqiu Jin; Ling Li (Journal of Contaminant Hydrology, 2026)

Salvianolic Acid B Inhibits Ferroptosis Through ACSL4 Pathway Regulation in sepsis-associated encephalopathy Mice - Xingyao Li; Zhizhun Mo; Yumei Yang; Chunxia Zhao; Shuwen Zhang; Yan Lin; Yuxiang Liu; Ling Wang; Xiaolong Xu; Qingquan Liu; Kai Fan (Molecular Neurobiology, 2026)

Presence and sources of antibiotics in Dongzhai Harbor, Hainan Island - Tuan-Tuan Wang; Hong-Jin Zhang; Tuan-Qi Guo; Jia-Yu Luo; Bi-Jiao Li; Wen-Qing Liao; Ling Mo; Sai Wang; Yue-Hua Huang (Marine Pollution Bulletin, 2025)

Endophytic Bacillus toyonensis D-6 via producing antifungal volatile organic compounds effectively controls green grape postharvest diseases - Lijun Ling; Wenyue Zhang; Rui Yue; Yijuan Jiang; Fanjin Kong; Rongxiu Mo; Lijun Feng; Yongpeng Zhou (Postharvest Biology and Technology, 2025)

Rainfall-dependent influence of water parameter interactions and land use on lake water quality: A hybrid ensemble approach and management implications - Jing Xu; Yuming Mo; Qihao Jiang; Lingzhong Kong; Jinran Wu; Zhe Ding; Guangqiu Jin; Ling Li (Journal of Hydrology, 2025)

Comparative study of hydrochemical characteristics and formation mechanisms of representative geothermal areas in Xinjiang area, Northwest China - Jiangyun Wang; Mo Xu; Chengpeng Ling; Haojie Cheng; Heng Zhang; Jian Guo (Geothermics, 2025)

Identification and exploration of sleep-enhancing peptides from goat milk casein by peptidomics and virtual screening - Ling Mo; Shan Wang; Beiqi Wu; Chaochao Zhao; Yimeng Yu; Jie Li; Hongxin Wang (Food Research International, 2025)

Advances in trans-scale RNA regulation and imaging - Mo-Fang Liu; Ling-Ling Chen; Yanyi Huang; Yangming Wang; Xiaofeng Cao (Science China Life Sciences, 2025)

PFKP Lactylation Promotes the Ovarian Cancer Progression Through Targeting PTEN - Jianfeng Mi; Ling Zhao; Yonglong Shen; Shien Mo; Yan Kuang (Biochemical Genetics, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Identification of pollution properties in typical tropical island watershed and their significant for source apportionment: A case study of Sanya, China - Chen Zhang; Yuanjun Peng; Xinzhi Li; Ling Mo; Licheng Wang; Zhiping Wang (Science of The Total Environment, 2025)

Effects of seawater salinity variations on nitrogen transport in the coastal reservoir and adjacent aquifer - Yuming Mo; Jing Xu; Kun Wang; Beibei Xu; Jinran Wu; Qihao Jiang; Guangqiu Jin; Ling Li (Journal of Hydrology, 2025)

Antifungal activity and application of Neurospora sitophila Y-4 against postharvest Penicillium italicum of Citrus reticulata 'Shiyue Ju' via 3-penten-2-one - Lijun Ling; Fanjin Kong; Yijuan Jiang; Wenyue Zhang; Rongxiu Mo; Rui Yue; Yao Li; Lijun Feng; Yongpeng Zhou (Food Bioscience, 2025)

Biodegradable polylactic acid (PLA) copolymer materials: Structural design, synthesis strategy, the relationship between structure and performance, industrial application - Rongrong Ji; Fan Mo; Linwei Liang; Chen Tian; Shixing Dong; Chang Deng; Hao Wu; Ling Zhou; Xipo Zhao (Chemical Engineering Journal, 2025)

Plastic film mulching ensures maize climate resilience: A perspective of temperature suitability and optimal sowing period window - Jing Wang; Ling Zhao; Bao-Zhong Wang; Fei Mo; Ning Wang; Shu-Tong Liu; Yuan Song; Ai-Tian Ren; Fu-Jian Mei; Yang Wang; Qi Lu; You-Cai Xiong (Soil and Tillage Research, 2025)

Interpretable machine learning models for predicting hormesis of binary antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Pei-Pei Zhang; Yan-Peng Liang; Hong-Hu Zeng; Yong-Hong Zhang; Li-Tang Qin (Journal of Hazardous Materials, 2025)

Regulating the gel structure and digestive function of myofibrillar protein: The distinct roles of pre-hydrated curdlan and β-glucan - Shuai Jiang; Rongyu Yan; Fan Mo; Qian Liu; Ling Jiang (Food Chemistry, 2025)

Improvement of coronary microcirculation in acute myocardial ischemia rats using a nanoscale carrier SiO2@PEG loaded with Nicorandil - Rui Wang; Yujing Mo; Yingcong Liang; Yuanhui Liu; Zhongchan Sun; Wenting Shang; Ling Xue (Drug Delivery and Translational Research, 2025)

Bacillus thuringiensis G-5 efficiently suppresses Codonopsis pilosula postharvest diseases by generating antifungal volatile organic compounds - Rongxiu Mo; Lijun Feng; Fanjin Kong; Yijuan Jiang; Wenyue Zhang; Lijun Ling (Antonie van Leeuwenhoek, 2025)

Enhancing arcade detection using bi-directed scene graphs with graph convolutional networks on street view imagery - Yi-Wen Mo; Chiao-Ling Kuo; Zhi-Sheng Lin (Remote Sensing Applications: Society and Environment, 2025)

Microbial distribution patterns and driving factors related to nitrogen cycling in karst Tiankeng soil - Xiaohui WANG; Junbo YANG; Keyi WANG; Danjuan ZENG; Ling MO; Gaozhong PU (Pedosphere, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Species-specific bioaccumulation and biotransformation of two novel brominated flame retardants in fish: Insights from isotope fractionation - Ling Mo; Guang-Yu Liao; Bin Tang; Cheng-Zhong Fu; Dong-Jing Zhou; Dong-Wei Du; Wei-Keng Luo; Rong-Fa Xu; Ming-Zhong Ren; Jing Zheng (Environmental Research, 2025)

Nitrogen-cycling microbial diversity and function in tiankengs at different evolutionary stages - Xiaohui Wang; Keyi Wang; Junbo Yang; Danjuan Zeng; Ling Mo; Gaozhong Pu (CATENA, 2025)

Unravelling the inhibition mechanism of 1-octene-3-ol combined with 3-heptene-2-one on Aspergillus flavus and its application in the preservation of wolfberries - Lijun Ling; Rongxiu Mo; Wenyue Zhang; Yijuan Jiang; Fanjin Kong; Lijun Feng; Yao Li; Rui Yue; Yongpeng Zhou (Postharvest Biology and Technology, 2025)

Higher N2O emissions and lower rice yield within double-cropped rice systems of South China under warming - Ting Bao; Nan Zhang; Danmei Mo; Zhuoshu Liu; Taotao Yang; Bin Zhang; Ling Wang; Haoyu Qian; Yanfeng Ding; Yu Jiang (Field Crops Research, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

O3–NOx–VOCs photochemical pollutant dispersion in 2D street canyon under effects of solar radiation - Jie Liang; Jian Hang; Shiguo Jia; Jiajia Hua; Bo Zhao; Xuelin Zhang; Hong Ling; Ziwei Mo (Atmospheric Environment, 2025)

Synergistic enhancement in ultra-trace thallium(I) removal using the titanium dioxide/biochar composite - Juanxi Huang; Jianying Mo; Ziyi Deng; Yirong Deng; Shenglin Mai; Yuan Xie; Canbin Zhong; Jianyou Long; Gaosheng Zhang; Ling Zhang; Tangfu Xiao; Huosheng Li (Journal of Environmental Management, 2025)

Presence and sources of per- and polyfluoroalkyl substances (PFASs) in the three major rivers on Hainan Island - Wang-Qing Tang; Tuan-Tuan Wang; Jiang-Wei Miao; Hua-Dong Tan; Hong-Jin Zhang; Tuan-Qi Guo; Zhong-Bing Chen; Chun-Yuan Wu; Ling Mo; Bi-Xian Mai; Sai Wang (Environmental Research, 2025)

ATP6V1B1 regulates ovarian cancer progression and cisplatin sensitivity through the mTOR/autophagy pathway - Shien Mo; Tingji Liu; Haiqin Zhou; Junning Huang; Ling Zhao; Fangfang Lu; Yan Kuang (Molecular and Cellular Biochemistry, 2025)
Early detection and effective chemotherapy for ovarian cancer, a serious gynecological malignancy, require further progress. This study aimed to investigate the molecular mechanism of ATPase H + -Transporting V1 Subunit B1 (ATP6V1B1) in ovarian cancer development and chemoresistance. Our data show that ATP6V1B1 is upregulated in ovarian cancer and correlated with decreased progression-free survival. Gain- and loss-of-function experiments demonstrated that ATP6V1B1 promotes the proliferation, migration, and invasion of ovarian cancer cells in vitro, while ATP6V1B1 knockout inhibits tumor growth in vivo. In addition, knocking down ATP6V1B1 increases the sensitivity of ovarian cancer cells to cisplatin. Mechanistic studies showed that ATP6V1B1 regulates the activation of the mTOR/autophagy pathway. Overall, our study confirmed the oncogenic role of ATP6V1B1 in ovarian cancer and revealed that ATP6V1B1 promotes ovarian cancer progression via the mTOR/autophagy axis.

Volatile organic compounds from Stenotrophomonas geniculata J-0 as potential biofumigants manage bulb rot caused by Fusarium oxysporum in postharvest Lanzhou lily - Lijun Ling; Rui Yue; Yuanyuan Wang; Lijun Feng; Ling Yang; Yao Li; Rongxiu Mo; Wenyue Zhang; Fanjin Kong; Yijuan Jiang; Yongpeng Zhou (World Journal of Microbiology and Biotechnology, 2025)

Heavy metal contamination of vegetables in China: status, causes, and impacts - Jing-Jing Feng; Jian-Xiong Liao; Qian-Wen Jiang; Ling Mo (Environmental Science and Pollution Research, 2024)

Habitat variations of sediment microbial community structure and functions and the influential environmental factors in a Ramsar protected wetland in South China - Kit-Ling Lam; Nora Fung-Yee Tam; Steven Jing-Liang Xu; Wing-Yin Mo; Yuet-Tung Tse; Kaze King-Yip Lai; Ping-Lung Chan; Fred Wang-Fat Lee (Marine Pollution Bulletin, 2024)

QSAR models for predicting key hormesis parameters of quinolone antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Xia-Chang-Li Xu; Li-Tang Qin; Fan Jiang (Science of The Total Environment, 2024)

Two new species of the subgenus Tipula (Emodotipula) Alexander, 1966 (Diptera, Tipulidae) from southwest China - Qi-Cheng Yang; Li-Ling Mo; Jing Wang; Xiao-Yan Liu; Ding Yang (Journal of Asia-Pacific Entomology, 2024)

Effect of solvents on structural stability and catalytic activity of Lipase Amano 30SD in EGCG esterification reaction estimated by FTIR and MD simulations - Shan Wang; Beiqi Wu; Ling Mo; Chaoyang Ma; Hongxin Wang (Food Bioscience, 2024)

Taxonomic and functional changes in wheat rhizosphere microbiome caused by imidazoline-based herbicide and genetic modification - Farman Ali; Zhaocheng Tang; Gangao Mo; Baolong Zhang; Xitie Ling; Zeyu Qiu (Environmental Research, 2024)

Industrial production of asymmetric wettability patterned fabric for efficient atmospheric water harvesting - Yuwei Guo; Ling Zhang; Canyu Shen; Liu Liu; Ruolian Mo; Ronghui Wu; Hongling Liu; Jianyong Yu (Chemical Engineering Journal, 2024)

Transcriptome profiling of longissimus dorsi during different prenatal stages to identify genes involved in intramuscular fat deposition in lean and obese pig breeds - Jun Feng Chen; Jing Wang; Jin Chai; Wei Jin; Qiao Ling Ren; Qiang Ma; Qing Xia Lu; Jia Jie Sun; De Lin Mo; Jia Qing Zhang; Bao Song Xing (Molecular Biology Reports, 2024)
Background There was significant difference in muscle development between fat-type and lean-type pig breeds. Methods and results In current study, transcriptome analysis and bioinformatics analysis were used to compare the difference in longissimus dorsi (LD) muscle at three time-points (38 days post coitus (dpc), 58 dpc, and 78 dpc ) between Huainan (HN) and Large white (LW) pig breeds. A total of 24500 transcripts were obtained in 18 samples, and 2319, 2799, and 3713 differently expressed genes (DEGs) were identified between these two breeds at 38 dpc, 58 dpc, and 78 dpc, respectively. And the number and foldchange of DEGs were increased, the alternative splice also increased. The cluster analysis of DEGs indicated the embryonic development progress of LD muscle between these two breeds was different. There were 539 shared DEGs between HN and LW at three stages, and the top-shared DEGs were associated with muscle development and lipid deposition, such as KLF4, NR4A1, HSP70, ZBTB16 and so on. Conclusions The results showed DEGs between Huainan (HN) and Large white (LW) pig breeds, and contributed to the understanding the muscle development difference between HN and LW, and provided basic materials for improvement of meat quality.

Insights into the in vitro digestibility and rheology properties of myofibrillar protein with different incorporation types of curdlan - Shuai Jiang; Fan Mo; Qian Liu; Ling Jiang (Food Chemistry, 2024)

The potential of glycinin basic peptide derived from soybean as a promising candidate for the natural food additive and preservative: A review - Hou-Qi Ning; Hai-Run Fan; Chun-Ling Yang; Gui-Jin Sun; Ying-Qiu Li; Hai-Zhen Mo (Food Chemistry, 2024)

Classification and regression machine learning models for predicting the combined toxicity and interactions of antibiotics and fungicides mixtures - Li-Tang Qin; Jun-Yao Zhang; Qiong-Yuan Nong; Xia-Chang-Li Xu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Environmental Pollution, 2024)

Photocarrier relay modulating solar CO2-to-syngas conversion - Qing Chen; Jia-Le Li; Qiao-Ling Mo; Fang-Xing Xiao (Chemical Engineering Journal, 2024)

Combined effects of nitrogen limitation and overexpression of malic enzyme gene on lipid accumulation in Dunaliella parva - Shi-Yu Liang; Li-Hua Li; Meng-Xiang Ling; Lei Mo; Li-Mei Huang; Ling-Ru Ruan; Chang-Hua Shang (Bioresource Technology, 2024)

Iron Overload Induces Hepatic Ferroptosis and Insulin Resistance by Inhibiting the Jak2/stat3/slc7a11 Signaling Pathway - Manqiu Mo; Ling Pan; Ling Deng; Min Liang; Ning Xia; Yuzhen Liang (Cell Biochemistry and Biophysics, 2024)

Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism and the Risk of Leukoaraiosis in a South Chinese Han Population: A Case–Control Study - Dong-can Mo; Xiao-ju Wu; Xiao-ling Li; Liu-yu Liu; Yi-ying Jiang; Guo-qiu Zhou; Li-jie Chen; Jiao-xing Li; Man Luo (Biochemical Genetics, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

Characteristic structures of liquid crystal monomers in EI-MS analysis and the potential application in suspect screening - Jing-Jing Feng; Jian-Xiong Liao; Qian-Wen Jiang; Ling Mo (Chemosphere, 2024)

Submerged plant-biochar composite system exhibits effective control over residual organic pollutants in the benthic organisms of aquaculture ponds - Juan-Ying Li; Siyu Yao; Zilong Mo; Yabo Miao; Yiqin Chen; Wenhui He; Ling Jin; Wenzhong Tang (Environmental Pollution, 2024)

Toxic interactions at the physiological and biochemical levels of green algae under stress of mixtures of three azole fungicides - Li-Tang Qin; Yu-Xue Lei; Min Liu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Science of The Total Environment, 2024)

Transcription and splicing variations of SR genes accompany with genome-wide accumulation of long-introns in pine - Shanlan Chen; Yingjie Zhang; Li Liu; Yujian Mo; Junyi Li; Beibei Chen; Yi Zhou; Jinxing Lin; Xingyu Jiang; Long Wei; Yu Ling (Plant Science, 2024)

Occurrence, distribution, and risk assessment of antibiotics in a typical aquaculture area around the Dongzhai Harbor mangrove forest on Hainan Island - Tuan-Tuan Wang; Shuai Shao; Shi-Di Fan; Wang-Qing Tang; Jiang-Wei Miao; Sai Wang; Xiao-Cong Cao; Chuan Liu; Guang-Guo Ying; Zhong-Bing Chen; Hai-Long Zhou; Xiao-Ping Diao; et al. (Science of The Total Environment, 2024)

Oral-based nanoparticle-wrapped dsRNA delivery system: a promising approach for controlling an urban pest, Blattella germanica - Gui-Jun Long; Xuan-Zheng Liu; Huan Guo; Meng-Qi Zhang; Lang-Lang Gong; Yun-Feng Ma; Youssef Dewer; Wu-Jia Mo; Ling-Wen Ding; Qin Wang; Ming He; Peng He (Journal of Pest Science, 2024)

Occurrence, multiphase partitioning, drivers, and ecological risks of current-use herbicides in a river basin dominated by rice–vegetable rotations in tropical China - Huadong Tan; Qiao Xing; Ling Mo; Chunyuan Wu; Xiaoying Zhang; Xiaoyu He; Yuefu Liang; Rong Hao (Science of The Total Environment, 2024)

Optimization of the manufacturing process and properties of alkali-activated palm oil fuel ash-based cold-bonded aggregates - Jiayi Lin; Tee How Tan; Jerome Song Yeo; Yingxin Goh; Tung-Chai Ling; Kim Hung Mo (Journal of Cleaner Production, 2024)

The Impact of Anthropogenic Pollution on Tidal Water Quality in Mangrove Wetlands - Kit-Ling Lam; Yu-Hin Lam; Angie Ying-Sim Ng; Ken Kwok-Yin So; Nora Fung-Yee Tam; Fred Wang-Fat Lee; Wing-Yin Mo (Journal of Marine Science and Engineering, 2023)
Mangrove wetlands are vulnerable coastal ecosystems that provide critical habitats for aquatic life. Tai O is a popular tourist village on Lantau Island, Hong Kong, which is surrounded by mangrove wetlands with rich biodiversity; and this village is also famous for its traditional stilt houses. However, the untreated municipal sewage from some stilt houses is directly discharged into nearby tidal channels, potentially threatening health of the adjacent mangrove wetlands. In order to evaluate the anthropogenic impact on these wetlands and identify the potential sources of their pollution, this study aimed to evaluate spatial (at the sampling points) and temporal (during weekdays and weekends) differences in the quality of their tidal water, and examine relationships between the water quality and the density of the stilt houses. The results indicated that the water quality was worse during weekends. The ammonia concentrations in most samples exceeded the limits of the Hong Kong Water Quality Objectives, China’s Sea Water Quality Standards, and even the U.S. EPA criterion for fish reproduction. This high ammonia input could potentially adversely affect the mangrove ecosystem, underscoring the need for further comprehensive studies. Moreover, some of the weekend water samples had lower dissolved oxygen levels and were polluted by phosphate. Our Principal Component Analysis revealed that water quality was correlated with stilt house density, suggesting that anthropogenic inputs of untreated sewage was the major source of pollution. These findings highlight that nutrients released from human activities, particularly ammonia and phosphate, must be controlled for a better protection of mangrove wetland ecosystems.

Thermal insulation performance of rock wool reinforced kaolinite-based porous geopolymer - Huixing Dai; Huan Gao; Pan Yang; Jinzong Mo; Haomin Zhang; Shengjun Lei; Ling Wang (Applied Clay Science, 2023)

Occurrence and ecological risks of flonicamid and its metabolites in multiple substrates from intensive rice–vegetable rotations in tropical China - Huadong Tan; Licheng Wang; Ling Mo; Chunyuan Wu; Qiao Xing; Xiaoying Zhang; Xiao Deng; Yi Li; Qinfen Li (Science of The Total Environment, 2023)

Identification and characterisation of microplastics released from plastic-coated paper cups using micro-Raman spectroscopy - Tianlong Zhang; Jia-Ling Hu; Yipin Duan; Sheng Chen; Dan Li; Ben Dong; Ming-Zhen Mo; Jing Wang; Jian-Guo Zheng; Huai-Ning Zhong; Qin-Bao Lin (Food Control, 2023)

Microwave catalytic co-pyrolysis of sugarcane bagasse and Chlorella vulgaris over metal modified bio-chars: Characteristics and bio-oil analysis - Song Qiu; Chunxiang Chen; Shouqiang Wan; Hongjian Ling; Yixue Wei; Shiyuan He; Haosen Shi; Xiankai Mo (Journal of Environmental Chemical Engineering, 2023)

Intra- and inter-habitat variation in sediment heavy metals, antibiotics and ecological risks in Mai Po RAMSAR, China - Kit-Ling Lam; Nora Fung-Yee Tam; Steven Jing-Liang Xu; Wing-Yin Mo; Ping-Lung Chan; Fred Wang-Fat Lee (Marine Pollution Bulletin, 2023)

Public perception of microplastics on a popular Chinese social media platform - Yinglin Wu; Donghui Mo; Jing Liu; Zitong Li; Xiaoli Chen; Ling Xie (Journal of Cleaner Production, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Spatio-temporal variation in water quality and phytoplankton community structure in Changwang, Meishe, and Wuyuan Rivers in Hainan Island, China - Edwine Yongo; Eunice Mutethya; Fangfang Jin; Pengfei Zhang; Sovan Lek; Ling Mo; Jingquan Li; Zhiqiang Guo (Environmental Monitoring and Assessment, 2023)

Strengthened public awareness of one health to prevent zoonosis spillover to humans - Yinglin Wu; Ling Luo; Yuxing Wang; Xiaoli Chen; Donghui Mo; Ling Xie; Aizhen Sun (Science of The Total Environment, 2023)

Evaluation of carbonation conversion of recycled concrete fines using high-temperature CO2: Reaction kinetics and statistical method for parameters optimization - Hamideh Mehdizadeh; Yuqing Wu; Kim Hung Mo; Tung-Chai Ling (Journal of Environmental Chemical Engineering, 2023)

Abundance and characteristics of microplastics in the Wanquan River estuary, Hainan Island - Tuan-Tuan Wang; Wang-Qing Tang; Dong-Hai Wu; Xin-Rui Yu; Guang-Yu Wang; Xing-Wei Cai; Shuai Shao; Sai Wang; Ling Mo; You-Sheng Liu; Guang-Guo Ying; Zhong-Bing Chen (Marine Pollution Bulletin, 2023)

Prediction of seismic acceleration response of precast segmental self-centering concrete filled steel tube single-span bridges based on machine learning method - Dan Zhang; Yuang Chen; Chen Zhang; Guixiang Xue; Junfei Zhang; Mo Zhang; Ling Wang; Ning Li (Engineering Structures, 2023)

Organic molecular markers in PM2.5 on a tropical island in the South China Sea: Temporal variations, sources, and process implications - Yuan Zeng; Zheng Liu; Yuxin Sun; Yufeng Guan; Yuqi Huang; Daning Li; Ling Mo; Shejun Chen; Bixian Mai (Atmospheric Pollution Research, 2023)

Divergent responses in the gut microbiome and liver metabolome to ammonia stress in three freshwater turtles - Qin-Yuan Meng; Dong-Mei Mo; Han Li; Wan-Ling Wang; Hong-Liang Lu (Science of The Total Environment, 2023)

Analysis of microplastics released from plastic take-out food containers based on thermal properties and morphology study - Jia-Ling Hu; Yipin Duan; Huai-Ning Zhong; Qin-Bao Lin; Tianlong Zhang; Chuang-Chuang Zhao; Sheng Chen; Ben Dong; Dan Li; Jing Wang; Ming-Zhen Mo; Jie Chen; et al. (Food Additives & Contaminants: Part A, 2023)

CO2-fixing and recovery of high-purity vaterite CaCO3 from recycled concrete fines - Hamideh Mehdizadeh; Kim Hung Mo; Tung-Chai Ling (Resources, Conservation and Recycling, 2023)

Correction to: Insights into sweet potato SR proteins: from evolution to species‑specific expression and alternative splicing - Shanlan Chen; Yujian Mo; Yingjie Zhang; Hongbo Zhu; Yu Ling (Planta, 2022)

Cocktail Formula and Application Prospects for Oral and Maxillofacial Organoids - Mingyu Ou; Qing Li; Xiaofang Ling; Jinguang Yao; Xiaoqiang Mo (Tissue Engineering and Regenerative Medicine, 2022)

Insights into sweet potato SR proteins: from evolution to species-specific expression and alternative splicing - Shanlan Chen; Yujian Mo; Yingjie Zhang; Hongbao Zhu; Yu Ling (Planta, 2022)

Study on the use of lightweight expanded perlite and vermiculite aggregates in blended cement mortars - Tzer Sheng Tie; Kim Hung Mo; U. Johnson Alengaram; Senthil Kumar Kaliyavaradhan; Tung-Chai Ling (European Journal of Environmental and Civil Engineering, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

A new abietane-type diterpenoid and a new long-chain alkenone from fungus Daldinia sp. TJ403-LS1 - Shuang Lin; Xueke Zhang; Ling Shen; Shuyuan Mo; Junjun Liu; Jianping Wang; Zhengxi Hu; Yonghui Zhang (Natural Product Research, 2022)

Efficient removal of Congo red with graphene aerogel derived from recycled anode of lithium-ion battery - Y. Zheng; X. Zhou; H. Luo; H. Ling; W. Mo; H. Fang; C. Shen; J. Lei; M. Sun; J. Li (International Journal of Environmental Science and Technology, 2021)

Resting-State MEG Source Space Network Metrics Associated with the Duration of Temporal Lobe Epilepsy - Junpeng Zhang; Jingwen Feng; Yifan Zhang; Site Mo; Jingjing Dong; Haitao Zhu; Ling Zhang; Ting Wu; Yuan Cui; Duo Chen (Brain Topography, 2021)

Effects of the Deep Pool on Groundwater Flow and Salinization in Coastal Reservoir and Adjacent Aquifer - Yuming Mo; Guangqiu Jin; Chenming Zhang; Jing Xu; Hongwu Tang; Chengji Shen; Alexander Scheuermann; Ling Li (Water Resources Management, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Proteomic Analysis of Serum Differentially Expressed Proteins Between Allergic Bronchopulmonary Aspergillosis and Asthma - Hui Cai; Diquan Shuai; Xiaomin Xue; Yuqing Mo; Xixi Song; Ling Ye; Shuiming Li; Daiwei Wang; Yun Wang; Meiling Jin (Mycopathologia, 2021)

Hepatitis A virus-induced hsa-miR-146a-5p attenuates IFN-β signaling by targeting adaptor protein TRAF6 - Ling Mo; Zhaoping Zeng; Rongzhen Deng; Zhiyuan Li; Jing Sun; Ningzhu Hu; Jiandong Shi; Yunzhang Hu (Archives of Virology, 2021)

Morphological and anatomical characteristics of exserted stigma sterility and the location and function of SlLst (Solanum lycopersicum Long styles) gene in tomato - Mo-zhen Cheng; Chao Gong; Bo Zhang; Wei Qu; Hao-nan Qi; Xiu-ling Chen; Xing-yuan Wang; Yao Zhang; Jia-yin Liu; Xiao-dong Ding; You-wen Qiu; Ao-xue Wang (Theoretical and Applied Genetics, 2021)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

First case of Shewanella indica isolated from a Bryde’s whale (Balaenoptera edeni) stranded in the northern Beibu Gulf, China - Jia Li; Richard W. McLaughlin; Mo Chen; Ying Li Liu; Hia Xia Xie; Xiao Ling Wan; Jun Ying Zhou; Jin Song Zheng (Antonie van Leeuwenhoek, 2020)

Genetic analysis and fine mapping of the gall midge resistance gene Gm5 in rice (Oryza sativa L.) - Hailian Zhou; Xinyi Wang; Yi Mo; Yang Li; Liuhui Yan; Zhihua Li; Wan Shu; Ling Cheng; Fengkuan Huang; Yongfu Qiu (Theoretical and Applied Genetics, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Characterization and application of a gall midge resistance gene (Gm6) from Oryza sativa ‘Kangwenqingzhan’ - Yang Li; Yi Mo; Zhihua Li; Meng Yang; Lihua Tang; Ling Cheng; Yongfu Qiu (Theoretical and Applied Genetics, 2020)

Sorting nexins, a component of retromer complex, interact with SRK in Brassica oleracea - Jing Zeng; Xiaoping Lian; Yan-ling Mo; Jingjing Chen; Yihua Liu; Liang Zhao; Liquan Zhu (Acta Physiologiae Plantarum, 2020)

MicroRNA-365 Knockdown Prevents Ischemic Neuronal Injury by Activating Oxidation Resistance 1-Mediated Antioxidant Signals - Jia-Lin Mo; Zhi-Guang Pan; Xiao Chen; Yu Lei; Ling-Ling Lv; Cheng Qian; Feng-Yan Sun (Neuroscience Bulletin, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

Involvement of glutamate receptors in regulating calcium influx in rice seedlings under Cr exposure - Yan-Hong Li; Xiao-Zhang Yu; Ling-Yun Mo; Yu-Juan Lin; Qing Zhang (Ecotoxicology, 2019)

Molecular cloning and expression analysis of SRLK1 gene in self-incompatible Asteraceae species Erigeron breviscapus - Wei Zhang; Mo Chen; Heng-ling Meng; Jin Yang; Xiang Wei; Sheng-chao Yang (Molecular Biology Reports, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Quantitative Vulnerability Model of Earth Dam Overtopping and its Application - Chong-Xun Mo; Gui-Yan Mo; Liu Peng; Qing Yang; Xin-Rong Zhu; Qing-Ling Jiang; Ju-Liang Jin (Water Resources Management, 2019)

Induction and identification of tetraploid Hedychium coronarium through thin cell layer culture - Hong-Yan Tu; Ai-Ling Zhang; Wang Xiao; Ya-Rou Lin; Jun-Hui Shi; Yong-Wei Wu; Si-Tong Wu; Chun-Hui Zhong; Shui-Xiu Mo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Molecular characterization of an imported dengue virus serotype 4 isolate from Thailand - Ling Mo; Jiandong Shi; Xiaofang Guo; Zhaoping Zeng; Ningzhu Hu; Jing Sun; Meini Wu; Hongning Zhou; Yunzhang Hu (Archives of Virology, 2018)

Effect of nicotine from tobacco root exudates on chemotaxis, growth, biocontrol efficiency, and colonization by Pseudomonas aeruginosa NXHG29 - Li Ma; Shuai Chao Zheng; Ti Kun Zhang; Zi Yi Liu; Xue Jian Wang; Xing Kui Zhou; Cheng Gang Yang; Jin Ling Duo; Ming He Mo (Antonie van Leeuwenhoek, 2018)

Bacillus zanthoxyli sp. nov., a novel nematicidal bacterium isolated from Chinese red pepper (Zanthoxylum bungeanum Maxim) leaves in China - Ma Li; Cao Yong Hong; Wang Xiao Yan; Zheng Shuai Chao; Yang Cheng Gang; Duo Jin Ling; Zhou Xing Kui; Xi Jia Qin; Zhu Ming Liang; Mo Ming He (Antonie van Leeuwenhoek, 2017)

Two-Stage Prediction on Effects of Mixtures Containing Phenolic Compounds and Heavy Metals on Vibrio qinghaiensis sp. Q67 - Ling-Yun Mo; Jie Liu; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Bulletin of Environmental Contamination and Toxicology, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Predicting the Binding Affinity of ERβ Ligands Based on a Novel Variable Selection Method - Hong-Yan Liu; Fei Zhang; Li-Tang Qin; Zhong-Sheng Yi; Xiu-Li Wang; Ling-Yun Mo (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Outbreak of Edwardsiella tarda infection in farm-cultured giant mottled eel Anguilla marmorata in China - Ze-Quan Mo; Ling Zhou; Xiang Zhang; Lian Gan; Li Liu; Xue-Ming Dan (Fisheries Science, 2015)

Linear regression model for predicting interactive mixture toxicity of pesticide and ionic liquid - Li-Tang Qin; Jie Wu; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2015)

Parallel simulation of groundwater flow in the North China Plain - Tangpei Cheng; Jingli Shao; Yali Cui; Zeyao Mo; Zhong Han; Ling Li (Journal of Earth Science, 2014)

Correlations Between CT Perfusion Parameters and Vascular Endothelial Growth Factor Expression and Microvessel Density in Implanted VX2 Lung Tumors - Shoujia Ling; Dong Deng; Yan Mo; Xiaobo Zhang; Xuechun Guan; Qijun Wei (Cell Biochemistry and Biophysics, 2014)

Analysis of sequence variability in the pig CART gene and association of polymorphism with fatness traits in a F2 population - Xiaoping Zhu; Delin Mo; Chong Wang; Xiaohong Liu; Jiaqi Li; Fei Ling; Yaosheng Chen (Molecular Biology Reports, 2014)

Impact of matrix metalloproteinase-8 gene variations on the risk of thoracic aortic dissection in a Chinese Han population - Xiao-Zeng Wang; Xiao-Mo Du; Quan-Min Jing; Xing-Xing Li; Ruo-Xi Gu; Jiao Wang; Ya-Ling Han (Molecular Biology Reports, 2013)

Microstructures and deformation mechanisms of hornblende in Guandi complex, the Western Hills, Beijing - XiaoLi Zhang; Ling Hu; Mo Ji; JunLai Liu; HongLin Song (Science China Earth Sciences, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

The process and mechanisms of metamorphism and deformation of hornblende—An example from the Hengshan Mountains, Shanxi Province - Mo Ji; Ling Hu; JunLai Liu; Liang Shen; YunXin Zou; HongLin Song; PeiSen Miao (Science China Earth Sciences, 2012)

Lysinibacillus mangiferahumi sp. nov., a new bacterium producing nematicidal volatiles - Ling-Ling Yang; Ying Huang; Jie Liu; Li Ma; Ming-He Mo; Wen-Jun Li; Fa-Xiang Yang (Antonie van Leeuwenhoek, 2012)

The Dayingzi detachment fault system in Liaodong Peninsula and its regional tectonic significance - Liang Shen; JunLai Liu; Ling Hu; Mo Ji; HuiMei Guan; Gregory A. Davis (Science China Earth Sciences, 2011)

Combined Toxicity of the Mixtures of Phenol and Aniline Derivatives to Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Shu-Shen Liu; Yi-Nian Zhu; Hai-Ling Liu; Hong-Yan Liu; Zhong-Sheng Yi (Bulletin of Environmental Contamination and Toxicology, 2011)

A novel direct equipartition ray design (EquRay) procedure for toxicity interaction between ionic liquid and dichlorvos - Rong-Ni Dou; Shu-Shen Liu; Ling-Yun Mo; Hai-Ling Liu; Fu-Cai Deng (Environmental Science and Pollution Research, 2011)

Specific cellular immune responses in mice immunized with DNA, adeno-associated virus and adenoviral vaccines of Epstein-Barr virus-LMP2 alone or in combination - Zhan Wang; SongMei Yang; Ling Zhou; HaiJun Du; WuNing Mo; Yi Zeng (Science China Life Sciences, 2011)

Variabilities of Two Drechslerella dactyloides Isolates in Korea and High Predacity Against Bursaphelenchus xylophilus - Zhen Wang; Chun-Yan Wang; Li-Juan Gu; Bai-Shen Sun; Dong-Liang Zhang; Lei Liu; Mi-Ra Lee; Chun-Ling Wang; Zheng Li; Eun-Kyung Mo; Chang-Keun Sung (Current Microbiology, 2011)

Consilience of genetics and archaeobotany in the entangled history of rice - Dorian Q. Fuller; Yo-Ichiro Sato; Cristina Castillo; Ling Qin; Alison R. Weisskopf; Eleanor J. Kingwell-Banham; Jixiang Song; Sung-Mo Ahn; Jacob van Etten (Archaeological and Anthropological Sciences, 2010)

Molecular cloning, expression patterns and subcellular localization of porcine TMCO1 gene - Zhisheng Zhang; Delin Mo; Peiqing Cong; Zuyong He; Fei Ling; Anning Li; Yuna Niu; Xiao Zhao; Chunyan Zhou; Yaosheng Chen (Molecular Biology Reports, 2010)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Arsenic exposure, urinary arsenic speciation, and the incidence of urothelial carcinoma: a twelve-year follow-up study - Yung-Kai Huang; Ya-Li Huang; Yu-Mei Hsueh; Mo-Hsiung Yang; Meei-Maan Wu; Shu-Yuan Chen; Ling-I Hsu; Chien-Jen Chen (Cancer Causes & Control, 2008)

Zearalenone (ZEN) detection by a single chain fragment variable (scFv) antibody - Shi-Hua Wang; Xiao-Yu Du; Ling Lin; Yu-Mo Huang; Zong-Hua Wang (World Journal of Microbiology and Biotechnology, 2008)

Sequence analysis of Arthrospira maxima based on fosmid library - Na Ling; Yunxiang Mao; Xuecheng Zhang; Zhaolan Mo; Guangce Wang; Wei Liu (Journal of Applied Phycology, 2007)